Eating and Lifestyle Habits in Youth With Down Syndrome Attending a Care Program: An Exploratory Lesson for Future Improvements - Roccatello, Giulia; Cocchi, Guido; Dimastromatteo, Rosa Tullia; Cavallo, Alessandra; Biserni, Giovanni Battista; Selicati, Mariella; Forchielli, Maria Luisa (Frontiers in Nutrition, 2021)
Introduction: Children with Down Syndrome (DS) have nutritional problems with unknown implications besides increased potential for obesity. Their food habits are unknown. We aim to delineate eating and lifestyle habits of DS children attending a multispecialist program to identify the challenges they face and the potential improvements. Patients and methods: We interacted with 34 DS children (22 males, 12 females, 2-16 years old) and their families. Food habits, medical conditions and treatments, degrees of development and physical activity, anthropometric and laboratory data were recorded over 6 months and analyzed. A 3-day food diary and a 24-hours recall food frequency questionnaire were administered. Results: Twentynine (85%) children completed meals, only 11 (32%) received alternative food such as milk. Weaning regularly started in 25 (73%) children. Preschool children introduced adequate calories and nutrients. School children and adolescents did not reach recommendations. All age groups, as the general pediatric population, excessively ate protein and saturated fat, and preferred bread, pasta, fruit juices, meat and cold cuts. Peculiarly, pulses and fish were adequately assumed by preschool and school children, respectively. Five children (15%) were overweight/obese. Conclusions: Dietary excesses commonly found in the general pediatric population are also present in this DS group, proving a narrowing gap between the two. DS group performed better nutritionally in the early years and overweight/obesity occurrence seems contained. DS children may benefit from a practical yet professional care-program in which nutrition education may improve their growth, development and transition into adulthood.